Streets as social spaces: evaluation of the Green Light Midtown Project, New York - Bhimarazu, Sravanti (Kansas State University, 2011)
This report evaluates the success of the Green Light for Midtown in New York in order to understand the factors that led to its success and thereby determine how social spaces can be created along streets and the initiatives that can be taken by other cities to create such spaces. It begins with a review of historical trends of urbanization that shifted the focus on streets from open spaces to transportation networks. The report attempts to answer a two-fold research question. Firstly, the Green Light for Midtown project in New York that attempted to reinvent the public space on Broadway and Times Square is evaluated in depth to examine the design elements that resulted in a thriving public space. This is done with the help of documents produced by the city and the concerned organizations as well as interviews with the officials in charge of the project. Analysis of the Green Light for Midtown illustrates certain elements that are essential for the design of social spaces along streets and bring the focus back on the pedestrians. Through the second part of the research question, the report attempts to determine the lessons that can be learnt from the New York example. The study reveals certain key elements for the creation of successful public spaces along streets in urban areas. The primary element is to have a political will that enable these changes to take place in the public realm. In addition, the area should be able to maintain a competitive edge in order to attract people and keep them coming back to the area. Finally, the regulations should be made more specific to the context of the area so that the identity of the place can be maintained effectively.
Keywords: Public Space; Urban Planning (0999)